PENGARUH INDEPENDENSI KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA - Kusumaningtyas, Metta (PRESTASI, 2012)
The objective of this study is to analyze the influence of audit committee independence and institutional ownership on earnings management. Institutional ownership is measured by the number of proportion of shares held by institutional shareholders divided by the number of shares issued. Earnings management in this study were measured by using the value of discretionary accrual. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2008-2009. Based on purposive sampling method, the number of samples in this study of 70 samples. Testing the hypothesis using multiple regression analysis. The results of hypothesis testing indicate that audit committee independence, had a significant negative effect on earnings management. Instead institutional ownership had not influence on earnings management.Keywords      :   earnings management, audit committee, insitutional ownership.